Immanent and diffractive critique in scholarship and publication - Bozalek, Vivienne; Romano, Nike (Critical Studies in Teaching and Learning, 2023)
Criticality  and  critique  require  careful  attention  by  authors,  reviewers,and  editors  in Critical Studies  in  Teaching  and  Learning(CRiSTaL),  since they  form  a  central  focus  of  the  journal. Conventional views of critique are influenced by unexpressed assumptions that what is needed is  an  authoritative  expert,  who  from  a  position  of  superiority  and  distance,  diagnoses  and pronounces on the inadequaciesof the text. This article explores more generative approaches to critique and criticality such as immanent critique and diffractive methodologies. We argue that in  order  for  immanent  critique  and  diffractive  methodologies  to  happen,  sensibilities  such  as attentiveness, response-ability, accountability, generosity,and curiosity are necessary. The final section of the paper considers academic practices of reviewing, writing, reading, pedagogy,and conferencing in relation to immanent critique and diffractive methodologies and the sensibilities we propose which make these forms of critique and criticality possible.